Auto-Masked Surface Texturing of Kerf-Loss Free Silicon Wafers Using Hexafluoroisopropanol in a Capacitively Coupled Plasma Etching System. (1st January 2019) - Kim, Suhyun; Park, Jin-Su; Kim, Jun-Hyun; Kim, Chang-Koo; Kim, Jihyun
Abstract : As the solar cell industry grows and receives worldwide attention for its sustainability, the consideration for its environmental impact becomes inevitable. The high global warming potential (GWP) of the fluorinated gases commonly used in a plasma processing is a significant environmental issue that needs to be addressed. Substituting the high GWP etchants with alternative gases could be an effective solution in plasma etching. Hexafluoroisopropanol (HFIP) not only has relatively low GWP and short atmospheric lifetime, but is also suitable for forming dense nanostructures on the silicon substrate. The morphology of the nanostructures fabricated on kerf-loss free (KLF) silicon substrates was changed by controlling the DC bias voltage of the capacitively coupled plasma etching system. The resulting reflectance spectra shows that HFIP/O2 plasma etching is highly effective in reducing the optical reflectivity loss of the silicon wafers. The suggested dry processing of KLF silicon wafers could improve both industrial and environmental sustainability of solar cell production.